2000
DOI: 10.3758/bf03212113
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic priming, neighborhood activation, and PARSYN

Abstract: Perceptual identification of spoken words in noise is less accurate when the target words are preceded by spoken phonetically related primes (Goldinger, Luce, & Pisoni, 1989).The present investigation replicated and extended this finding. Subjects shadowed target words presented in the clear that were preceded by phonetically related or unrelated primes. In addition, primes were either higher or lower in frequency than the target words. Shadowing latencies were significantly longer for target words preceded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
184
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(199 citation statements)
references
References 26 publications
9
184
0
3
Order By: Relevance
“…According to Goldinger et al, a model in which frequency operates directly on activation levels (either on resting activations or connection weights) would predict more inhibition from high-frequency primes than from lowfrequency primes because high-frequency primes should produce stronger competing activation. However, Luce, Goldinger, Auer, and Vitevitch (2000) reported simulations with a connectionist model (''PARSYN'') in which frequency is instantiated in connection strengths (i.e., the weights of lateral connections between phonemes are proportional to forward and backward transitional probabilities), which correctly predicted the trend for stronger priming by low-frequency items. As Luce et al note, PARSYN is similar to a class of models, including TRACE, which presumably would make similar predictions.…”
Section: Hf-lf (Section)mentioning
confidence: 99%
“…According to Goldinger et al, a model in which frequency operates directly on activation levels (either on resting activations or connection weights) would predict more inhibition from high-frequency primes than from lowfrequency primes because high-frequency primes should produce stronger competing activation. However, Luce, Goldinger, Auer, and Vitevitch (2000) reported simulations with a connectionist model (''PARSYN'') in which frequency is instantiated in connection strengths (i.e., the weights of lateral connections between phonemes are proportional to forward and backward transitional probabilities), which correctly predicted the trend for stronger priming by low-frequency items. As Luce et al note, PARSYN is similar to a class of models, including TRACE, which presumably would make similar predictions.…”
Section: Hf-lf (Section)mentioning
confidence: 99%
“…In addition, spurious word forms that span existing word boundaries (such as speech in grasp each) may correspond to lexical items and lead to their activation in the candidate set (Gow & Gordon, 1995;Shillcock, 1990;Tabossi, Burani, & Scott, 1995;Vroomen & de Gelder, 1997). Consequently, other models have assumed that lexical candidates can be activated at any point in the speech stream (Luce, Goldinger, Auer, & Vitevitch, 2000;McClelland & Elman, 1986;Norris, 1994). Indeed, many words are apparently not properly identified until after their acoustic offset (Allopena, Magnuson, & Tanenhaus, 1998;Goldinger, Luce, & Pisoni, 1989;Luce et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, other models have assumed that lexical candidates can be activated at any point in the speech stream (Luce, Goldinger, Auer, & Vitevitch, 2000;McClelland & Elman, 1986;Norris, 1994). Indeed, many words are apparently not properly identified until after their acoustic offset (Allopena, Magnuson, & Tanenhaus, 1998;Goldinger, Luce, & Pisoni, 1989;Luce et al, 2000). In any case, the competition among the activated candidates winnows the set to the word that is ultimately extracted and recognized.…”
Section: Introductionmentioning
confidence: 99%
“…This divide is mirrored in models of spoken-word recognition. In most models (e.g., Lahiri & Reetz, 2002;Luce, Goldinger, Auer, & Vitevitch, 2000;McClelland & Elman, 1986 /eix=l=k/ 'actually' and natuurlijk /natyrl=k/ 'naturally'. Ernestus (2000) showed that these forms may be pronounced as [eik] and [tyk] in casual speech.…”
Section: Introductionmentioning
confidence: 99%